2019
DOI: 10.1002/ente.201800919
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Carbon@NiCo2O4 Core–Shell Microspheres for Efficient Electrocatalytic Oxygen Evolution

Abstract: Earth‐abundant transition metal oxides are considered one of the most promising oxygen evolution reaction (OER) catalysts. However, their intrinsically low electrical conductivity inhibits the fast kinetics for OER. To overcome this drawback, hollow carbon@NiCo2O4 core–shell microspheres (C@NiCo2O4 HSs) are synthesized with enhanced electrocatalytic activity and stability toward OER. The prepared C@NiCo2O4/Ni foam delivers a current density of 10 mA cm−2 at a small overpotential of 268 mV and exhibits a low Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Among these catalysts, RuO 2 and IrO 2 as the representative OER catalysts have exhibited the excellent catalytic performance toward water oxidation, but the expensive cost and deficiency greatly limit its widespread application . Therefore, countless efforts have been devoted to fabricate the efficient and alternative OER cocatalysts to improve the PEC water splitting efficiency, such as transition metal oxides, metallic hydroxides, and C‐doped nanomaterials . Among these materials, the hot topic of metallic hydroxides in the field of catalysis has demonstrated that some metal atoms could show excellent OER catalytic activity, which results from the abundant metal sites acted as the active center .…”
Section: Introductionmentioning
confidence: 99%
“…Among these catalysts, RuO 2 and IrO 2 as the representative OER catalysts have exhibited the excellent catalytic performance toward water oxidation, but the expensive cost and deficiency greatly limit its widespread application . Therefore, countless efforts have been devoted to fabricate the efficient and alternative OER cocatalysts to improve the PEC water splitting efficiency, such as transition metal oxides, metallic hydroxides, and C‐doped nanomaterials . Among these materials, the hot topic of metallic hydroxides in the field of catalysis has demonstrated that some metal atoms could show excellent OER catalytic activity, which results from the abundant metal sites acted as the active center .…”
Section: Introductionmentioning
confidence: 99%